Utilization of Reformed Coconut Fiber and Banana Stem Fibre as Green Oil Sorbent. Issue 15 (23rd November 2022) - Madasamy, Sankaranarayanan; Ramasubbu, Rajkumar; Nambirajan, Naganambi
ABSTRACT: Oil spillage is one of the significant wellsprings of contamination. It can happen in both land and water. Their expulsion from marine and land environment is regularly difficult. This investigation considers the utilization of coconut and banana stem fibers as a feasible sorbent material for marine and land oil spill recuperation. Coconut and banana stem fibers have lumens, which increases their specific surface area available for oil sorption. These fibers are cheap and have low bulk density, which makes them reasonable for oil spill recuperation. Moisture content in coconut and banana stem fiber were found to be 4.44% and 5.44%, respectively. The oil sorption limit of coconut and banana stem fiber was improved by coating it with chitosan. The treated fibers showed a considerable enhancement in oil sorption capacity for coconut fiber (9.87%) and banana stem fiber (6.59%), according to the results. The characterization of the natural and coated fibers was completed utilizing scanning electron microscopy and Fourier transform infrared spectroscopy. Moisture content and oil sorption limit of the fibers were estimated. The test has confirmed that both cocont and banana stem fibers can be utilized as a potential sorbent material for oil spillage tidy up.